Speaking difficulties of grade 9 students of Balaoan Districy - Sabado, Gloria Antonette O. (City of San Fernando, La Union : [s.n.], 2018)
This descriptive research determined the speaking difficulties of Grade 9 students of Balaoan District during the School Year 2017-2018 and the factors affecting their speaking skills of the School Year 2017-2018. A total of 50 Grade 9 students participated in the study. Data gathered using an oral test and group interview were treated using frequency, percentage, and ranking. Data gathered revealed that the Grade 9 students have the most difficulty in pronouncing words with fricative sounds followed by their difficulty in uttering diphtongs, vowel and consonant sounds. A validated Oral Skill Book was crafted and proposed by the researcher to help enchance the speaking skills of the Grade 9 students.
Bibliography: various pagination.
CHED-La Union
Keywords: Public speaking